Low-thermal-budget Au-free ohmic contact to an ultrathin barrier AlGaN/GaN heterostructure utilizing a micro-patterned ohmic recess. (September 2021) - Shi, Wen; Huang, Sen; Wang, Xinhua; Jiang, Qimeng; Yao, Yixu; Bi, Lan; Li, Yuchen; Deng, Kexin; Fan, Jie; Yin, Haibo; Wei, Ke; Li, Yankui; et al.
Abstract: A pre-ohmic micro-patterned recess process, is utilized to fabricate Ti/Al/Ti/TiN ohmic contact to an ultrathin-barrier (UTB) AlGaN/GaN heterostructure, featuring a significantly reduced ohmic contact resistivity of 0.56 Ω·mm at an alloy temperature of 550 °C. The sheet resistances increase with the temperature following a power law with the index of +2.58, while the specific contact resistivity decreases with the temperature. The contact mechanism can be well described by thermionic field emission (TFE). The extracted Schottky barrier height and electron concentration are 0.31 eV and 5.52 × 10 18 cm −3, which suggests an intimate contact between ohmic metal and the UTB-AlGaN as well as GaN buffer. A good correlation between ohmic transfer length and the micro-pattern size is revealed, though in-depth investigation is needed. A preliminary CMOS-process-compatible metal–insulator–semiconductor high-mobility transistor (MIS-HEMT) was fabricated with the proposed Au-free ohmic contact technique.